Accelerating the rate of improvement in cystic fibrosis care: contributions and insights of the learning and leadership collaborative. (7th March 2014) - Godfrey, Marjorie M; Oliver, Brant J
Abstract : Introduction: The Learning and Leadership Collaborative (LLC) supports cystic fibrosis (CF) centres' responses to the variation in CF outcomes in the USA. Between 2002 and 2013, the Cystic Fibrosis Foundation (CFF) designed, tested and modified the LLC to guide front line staff efforts in these efforts. This paper describes the CFF LLC evolution and essential elements that have facilitated increased improvement capability of CF centres and improved CF outcomes. Methods: CF centre improvement teams across the USA have participated in 11 LLCs of 12 months' duration since 2002. Based on the Dartmouth Microsystem Improvement Curriculum, the original LLC included face to face meetings, an email listserv, conference calls and completion of between learning session task books. The LLCs evolved over time to include internet based learning, an electronic repository of improvement resources and examples, change ideas driven by evidence based clinical practice guidelines, benchmarking site visits, an applied QI measurement curriculum and team coaching. Results: Over 90% of the CF centres in the USA have participated in the LLCs and have increased their improvement capabilities. Ten essential elements were identified as contributors to the successful LLCs: LLC national leadership and coordination, local leadership, people with CF and families involvement, registry data transparency, standardised improvement curriculum with evidence based change ideas, internet resources with reminders, team coaching, regular progress reporting and tracking, benchmarking site visits and applied improvement measurement. Conclusions: The LLCs have contributed to improved medical and process outcomes over the past 10 years. Ten essential elements of the LLCs may benefit improvement efforts in other chronic care populations and health systems.